Fine Needle Aspiration Cytology (FNAC): An Effective, Less Invasive Preoperative Diagnostic Technique for Breast Lesions - Ogenyi, Samuel Ifedioranma; Okani, Chukwudi Onyeaghana; Unachukwu, Ifechukwu Chisomeje; Onu, June Amara; Ike, Amalachukwu Okwukwe; Nyenke, Clement Ugochukwu (Asian Pacific Journal of Cancer Biology, 2024)
Background /Introduction: With the increasing incidence of breast cancer, the need for minimally invasive, prompt, cost effective and definitive preoperative assessment of breast lesions using fine needle aspiration cytology (FNAC) may be explored, especially in a developing country. The study was out to classify a broad spectrum of breast lesions diagnosed using FNAC, to determine the prevalence and highlight the efficacy of FNAC in breast lesion diagnosis. Materials and Methods: One hundred and thirty one (131) patients who presented to the Histopathology department of Chukwuemeka Odumegwu Ojukwu University Teaching Hospital, Awka, from 2014 to December 2019 were utilized for this study. Patients’ data and investigation reports were retrieved from the hospital records and laboratory report register. Ethical approval for the study was obtained from the ethics committee of COOUTH, Awka (Ref number: COOUTH/CMAC/ETH.C/VOL 1/FN: 04/0063). Results: The study revealed that seven males (5.4%) and 124 (94.7%) females, with a mean age of 45years presented within the time frame. Benign and malignant lesions accounted for 41.2% (54) and 38.9% (51) respectively, of the total population while inflammatory lesions, ductal carcinoma, Lymphadenitis, chronic abscess and fibro-adenoma accounted for 16.72% (22). Four cases (3.1%) fell into the category of insufficient cells for cytological analysis (C1). Seventy four patients (56.5%) presented with right breast lumps, 48(36.6%) left breast, while 9 (6.9%) presented with lumps on both breasts. Patient with age range of 51-60 years had most frequent malignant cases. Besides, varying clinical presentation of the lumps was observed. Conclusions and Recommendations: Definite diagnosis of malignant breast lesions using FNAC could suggest efficacy, reliability and acceptability of the technique for definitive and early breast lesions diagnosis. Therefore, to enhance early and definitive diagnosis of breast lesions, which is a key factor in management and event free survival rate, FNAC; a less invasive, patients’ acceptable diagnosis technique is advocated.